2023
DOI: 10.4102/phcfm.v15i1.3777
|View full text |Cite
|
Sign up to set email alerts
|

Facilitators and barriers to in vitro diagnostics implementation in resource-limited settings: A scoping review

Abstract: Low-and middle-income countries.Methods: This scoping review was guided by Arksey and O'Malley's methodological framework. A comprehensive keyword search for literature was conducted in Google Scholar, EBSCOhost, PubMed, Web of Science and ScienceDirect using the Boolean terms ('AND' and 'OR'), as well as Medical Subject Headings. The study considered published articles in the English language from 2016 to 2021 and was limited to qualitative, quantitative and mixed-method studies. Two reviewers independently s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 54 publications
(130 reference statements)
1
9
0
Order By: Relevance
“…Like Huddy et al’s study, this study found that POC testing provides rural practice with access to diagnostic investigations [ 20 ]. This study supported Martin et al’s study on facilitators and barriers to POC testing for sexually transmitted infections in LMICs, and Ansu-Mensah et al’s study on facilitators and barriers to in vitro diagnostics implementation in a resourced-limited setting which reported several barriers to POC testing implementation [ 16 , 17 ].…”
Section: Discussionsupporting
confidence: 85%
See 4 more Smart Citations
“…Like Huddy et al’s study, this study found that POC testing provides rural practice with access to diagnostic investigations [ 20 ]. This study supported Martin et al’s study on facilitators and barriers to POC testing for sexually transmitted infections in LMICs, and Ansu-Mensah et al’s study on facilitators and barriers to in vitro diagnostics implementation in a resourced-limited setting which reported several barriers to POC testing implementation [ 16 , 17 ].…”
Section: Discussionsupporting
confidence: 85%
“…A qualitative study was employed following a quantitative study to explore the availability, stock levels, and usage of POC tests at the CHPS facilities in the rural areas of the Bono Region [5]. The region is one of the newly created regions in Ghana with few hospitals.…”
Section: Study Design and Settingmentioning
confidence: 99%
See 3 more Smart Citations